Peningkatan Hasil Belajar Siswa Menggunakan Media Pembelajaran Canva Pada Mata Pelajaran Qurdis di SD Al-Furqon 2 Wedoroanom Driyorejo Gresik - Nevia Dina Trianingrum; Ach. Khusnan; Barudin (Jurnal Pendidikan Agama Islam Miazhar, 2024)
This research is motivated by the fact that student learning outcomes in class 2 SD Al-Furqon 2 Wedoroanom Driyorejo Gresik are still relatively low in the Qurdis subject. Teachers are expected to improve student learning outcomes. Improving student learning outcomes is carried out by utilizing the Canva application-based learning media which makes it possible to apply it very effectively to learning the Quran Hadith. This study aims to 1) Know the application of Canva learning media to grade 2 students in the Quran Hadith subject at SD Al-Furqon 2 Wedoroanom Driyorejo Gresik. 2) Knowing the learning outcomes of grade 2 students in the Quran Hadith subject through the application of canva learning media at SD Al-Furqon 2 Wedoroanom Driyorejo Gresik. The research method used in this research is Classroom Action Research. Where this type of PTK consists of 4 stages namely, planning, implementation, observation, and action/reflection. These stages are carried out in 2 cycles. The subjects of this research were the 2nd grade students of SD Al-Furqon 2 Wedoroanom Driyorejo Gresik. The data collection technique used was observation using teacher and student observation sheets, learning achievement tests and documentation. The results of this study can be explained as follows: In cycle I of 31 students there were 19 students or 61% who completed in the moderate category but were lacking, while 12 students did not complete, and cycle II there was an increase with 26 students or 83, 8% who completed were in the very good category while there were 5 students who did not complete. So, it can be concluded that from cycle I to cycle II the completeness of learning outcomes has increased significantly. Thus the Canva learning media can improve student learning outcomes in the Quran Hadith subject material for Surat al-Qariah for grade 2 SD Al-Furqon 2 Wedoroanom Driyorejo Gresik.